Síntesis y caracterización de un hidrogel electroresponsivo para un sistema de liberación controlada de fármacos (2021)
(ing) Controlled drug release (CDL) systems are those that seek to release a drug at a predetermined rate, locally or systemically, with predictable kinetics and for a specific period. These systems aim to improve the effectiveness of therapy, reduce drug side effects and reduce the doses required during treatment. There are various materials used as carriers in the LCF, such as polymers, carbon dots, or liposomes. Currently, polymeric hydrogels are used to perform this task, which are three-dimensional networks capable of holding a large amount of an aqueous solvent. This allows them to have very flattering properties such as absorption, swelling and deswelling behavior, and hydrophilicity. As a result, in the LCF there is a particular interest in implementing hydrogels sensitive to physical, chemical and biological, since they enable the release of the necessary amount of drug according to the specific conditions of the body. Among these hydrogels are the electroresponsive ones made from natural or synthetic polymers with high concentrations of ionizable groups. These change their properties to counteract an applied electrical current; thus, they can swell, contract, or bend with small changes in the supplied current. Thus, considering and manipulating the electric field as an external stimulus offers advantages such as precise control of the magnitude of the current, the duration of the electric pulses and the interval between pulses. Taking into account the excellent properties and characteristics of polymeric hydrogels, this research sought to synthesize and characterize an electroresponsive hydrogel based on DEXTRAN and aniline tetramers as a potential vehicle for controlled drug release. In that order of ideas, the work had three stages: the first was the synthesis and characterization of the electroresponsive hydrogel based on DEXTRAN (polymer natural) and aniline tetramers, here absorption and infrared spectra were taken, and thermal stability, swelling radius and conductivity tests were performed; the second was the evaluation of the electrical behavior of the electroresponsive hydrogel; and, finally, a literature review was carried out for the development of mechanical and electrical characterization protocols.